A longitudinal molecular study of the ecology of malaria infections in free-ranging mandrills. (December 2019) - Charpentier, M.J.E.; Boundenga, L.; Beaulieu, M.; Dibakou, S.E.; Arnathau, C.; Sidobre, C.; Willaume, E.; Mercier-Delarue, S.; Simon, F.; Rougeron, V.; Prugnolle, F.
Abstract: Unravelling the determinants of host variation in susceptibility and exposure to parasite infections, infection dynamics and the consequences of parasitism on host health is of paramount interest to understand the evolution of complex host-parasite interactions. In this study, we evaluated the determinants, temporal changes and physiological correlates of Plasmodium infections in a large natural population of mandrills ( Mandrillus sphinx ). Over six consecutive years, we obtained detailed parasitological and physiological data from 100 male and female mandrills of all ages. The probability of infection by Plasmodium gonderi and P. mandrilli was elevated (ca. 40%) but most infections were chronical and dynamic, with several cases of parasite switching and clearance. Positive co-infections also occurred between both parasites. Individual age and sex influenced the probability of infections with some differences between parasites: while P. mandrilli appeared to infect its hosts rather randomly, P. gonderi particularly infected middle-aged mandrills. Males were also more susceptible to P. gonderi than females and were more likely to be infected by this parasite at the beginning of an infection by the simian immunodeficiency virus. P. gonderi, and to a lesser extent P. mandrilli, influenced mandrills' physiology: skin temperatures and neutrophil/lymphocyte ratio were both impacted, generally depending on individual age and sex. These results highlight the ecological complexity of Plasmodium infections in nonhuman primates and the efforts that need to be done to decipher the epidemiology of such parasites. Graphical abstract: Copyright: B. Quintard Image 1 Highlights: Longitudinal epidemiological and physiological data on Plasmodium infection obtained from a wild primate population. Elevated chronical infections by two species of Plasmodium . Contrasted dynamics of infection and physiological effects of P. gonderi and P. mandrilli . Elevated parasitaemia ( P. gonderi ) in male mandrills in primo-infection by the simian immunodeficiency virus.